Developing and Testing Hybrid Glass to Steel Structural Elements – Flexible Design Approach - Trajanoska, Bojana; Gavriloski, Viktor; Doncheva, Elisaveta (Advanced Technologies and Materials, 2023)
Structural integrity of elements depends on their geometry, function and connections used between them. In this paper new hybrid glass to steel elements are investigated concerning their mechanical behavior and function which directly influences their design and vice versa. Their basic design is tested experimentally and then a flexible design approach including parametrical study is proposed for developing unique structural elements for different application. The concept design takes advantage of the mechanical properties of tempered glass, steel and polymer adhesive and achieves structural geometry which results in high mechanical, structural and architectural potential.